Comparative Study of Integrated Pest Management and Farmer's Standard Practices for Controlling Chrysanthemum Thrips under Plastic House - Hutapea, Dedi; Sartiami, Dewi; Dadang, Dadang; Hidayat, Purnama (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Thrips is an important worldwide cause of severe damage to various host plants, especially chrysanthemums. Current management still relies on synthetic insecticides to control thrips. However, these pesticides harm the environment and promote thrips resistance. The study aimed to compare integrated pest management (IPM) and farmer’s standard practices to control Thrips parvispinus on two chrysanthemum varieties and calculate the cost-benefit ratio of both pest control practices. Two chrysanthemum cultivars were planted in plastic houses to compare IPM and farmer’s standard practices. The observed variables included thrips density, attack and damage rates, cut flower yield, and natural enemies abundance. Data were analyzed using ANOVA, and Tukey's HSD test identified significant differences at a 5% level. The results showed that the population of T. parvispinus nymphs was higher (78%) than adults. The highest adult thrips population emerges when chrysanthemums achieve the flowering phases. This study reveals that the control effects of IPM were not different from farmer’s standard practices. A holistic approach integrating several management strategies successfully controlled the thrips population while producing high-quality crops with minimal aesthetic damage. The IPM strategy against thrips showed a competitive cost and reduced synthetic insecticide applications without decreasing the quality and productivity of chrysanthemums.